Kidney transplantation between identical twins with APOL1 homozygote risk alleles – a case report - Sean Lei; Abhirami Shankar; Supreet Sethi; Erik L. Lum (Frontiers in Nephrology, 2025)
Kidney transplantation is the optimal therapy for individuals with end-stage kidney disease. Recent studies suggest a negative impact of high-risk Apolipoprotein L1 genotypes on outcomes for both living kidney donors and kidney transplant recipients. In this case, we describe a pair of identical twins with a high-risk APOL1 genotype who underwent successful living kidney transplantation with excellent short-term outcomes.